Mangrove Biodiversity In Tatengesan Village, Pusomaen District, Southeast Minahasa - Nofia Poluan; Helen Joan Lawalata; Wiesye Maya Selfia Nangoy; Meity Neltje Tanor; Rievo Handry Djarang (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Mangrove forest is a type of forest that grows in coastal areas and river estuaries and has three functions, namely ecological, social, and economic functions. The purpose of this study was to determine the level of diversity of mangrove species in Tatengesan Village, Pusomaen District, Southeast Minahasa Regency. Observations were made on a transect with a size of 50 x 25 m consisting of 4 plots. Mangrove sampling was carried out using a plot with a size of 10 x 7 m, using a purposive sampling method. Ecological index analysis includes species diversity, uniformity, and dominance. There are 7 mangrove species namely Bruguiera gymnnorhiza, Rhizophora mangle, Kandelia obovata, Avicennia marina, Rhizophora mucronata, Languncularia racemose, and Ceriops tagal. The species diversity index at the biological level is low.